Antibacterial Activity of the Roots of Medicinal Plant Catharanthus roseus (L) - Komal Tikariya; Rajat Pawar; Nisha Mandloi; Shivam Soni; Kamna Tripathi; Rinku Dhakad; Shikha Nagle bhati; Chanchal Navin Raj (The Bioscan, 2024)
Medicinal plants have been used in healthcare since time immemorial. Studies have been carried out globally to verify their efficacy and some of the findings have led to the production of plant-based herbal medicines. Many of these herbal medicines have beneficial effects on long- term health when consumed by humans, and can be used to effectively treat human diseases. Thepresent study aimed at, phytochemical screening, Antioxidant activity of ethanolic extract at varying concentration invitro and biological studies of the medicinal plant Cantharanthus roseus (L). This plant are very less explored and found in particular region, while large number of plants from this genera have been studied and proven to have number of phytoconstituents and biological activities. The phytochemical screening of Plant roots extract showed the presence of phytochemically active compounds such as tannin, flavonoids, steroids, terpenoids, triterpeniods, alkaloids, anthraquinones, polyphenol, glycosides in higher percentage. The antibacterial studies on the ethanolic extract of plant name Cantharanthus roseus(L) have been carried out six pathogenic bacteria including gram positive and negative. They found to have moderate antibacterial activities.